2010
DOI: 10.1371/journal.pone.0008642
|View full text |Cite
|
Sign up to set email alerts
|

Acute Administration of Non-Classical Estrogen Receptor Agonists Attenuates Ischemia-Induced Hippocampal Neuron Loss in Middle-Aged Female Rats

Abstract: BackgroundPretreatment with 17β-estradiol (E2) is profoundly neuroprotective in young animals subjected to focal and global ischemia. However, whether E2 retains its neuroprotective efficacy in aging animals, especially when administered after brain insult, is largely unknown.Methodology/Principal FindingsWe examined the neuroprotective effects of E2 and two agonists that bind to non-classical estrogen receptors, G1 and STX, when administered after ischemia in middle-aged rats after prolonged ovarian hormone w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
109
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(124 citation statements)
references
References 54 publications
10
109
2
3
Order By: Relevance
“…Along these lines, our study found that low-dose E2 replacement in middle-aged rats was capable of exerting significant neuroprotection against GCI, in contrast to a lack of protection in old rats. Our finding that E2 is still protective in middle-aged rats is consistent with previous reports by others in both focal and GCI models (33)(34)(35). Low-dose E2 therapy would be preferred in humans so as to minimize negative side effects.…”
Section: Discussionsupporting
confidence: 92%
“…Along these lines, our study found that low-dose E2 replacement in middle-aged rats was capable of exerting significant neuroprotection against GCI, in contrast to a lack of protection in old rats. Our finding that E2 is still protective in middle-aged rats is consistent with previous reports by others in both focal and GCI models (33)(34)(35). Low-dose E2 therapy would be preferred in humans so as to minimize negative side effects.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with previous reports in OVX rodents. 8,9,21 By contrast, G-1 treatment had no effect on stroke outcome in intact females, in which GPER occupancy would presumably be opposed by high levels of circulating and bound estrogen, analogous to observations that estrogen supplementation has little or no neuroprotective effects after stroke in intact females. 22 These findings highlight the complex nature of endogenous estrogen signaling, which may involve 3 receptor types and vary between different physiological and disease settings, and they reinforce the body of evidence indicating that effects of estrogen in the female brain are not necessarily transferrable to males.…”
Section: Strokementioning
confidence: 66%
“…Through genomic and nongenomic mechanisms, E2 modulates neuronal excitability and rapidly increases signal transmission by regulating both NMDA and non-NMDA glutamate receptors (NMDARs) (Wong and Moss, 1992;Foy et al, 1999). The GPR30 receptor may act together with intracellular estrogen receptors to activate cell-signaling pathways to promote neuron survival after global ischemia (Hazell et al, 2009;Gingerich et al, 2010;Lebesgue et al, 2010). However, the role of GPR30 in neuroprotection against excitotoxic neuronal death induced by NMDA exposure remains unknown.…”
Section: Introductionmentioning
confidence: 99%